Extracorporeal shock wave therapy for chronic calcific tendinitis of the shoulder: single blind study. Issue 3 (1st March 2003) - Cosentino, R; De Stefano, R; Selvi, E; Frati, E; Manca, S; Frediani, B; Marcolongo, R
Abstract : Objective: To evaluate the clinical and radiological response of chronic calcific tendinitis of the shoulder to extracorporeal shock wave therapy (ESWT) in a single blind study. Methods: 70 patients showing chronic, symptomatic, calcifying tendinitis of the shoulder were examined. A single blind randomised study was performed with 35 patients undergoing a regular treatment (group 1) and 35 a simulated one (group 2). Pain and functional assessment was carried out according to Constant and Murley. Variations in the dimension of the calcification were evaluated by anteroposterior x ray films. Results: A significant decrease of pain and a significant increase in shoulder function was seen in group 1. Examination by x ray showed partial resorption of the calcium deposits in 40% of cases and complete resorption in 31% of cases in group 1. In the control group no significant decrease of pain and no significant increase in shoulder function was seen. No modifications were observed by x ray examination. Conclusion: Because of its good tolerance, safety, and clinical radiological response, ESWT can be considered as an alternative treatment for chronic calcific tendinitis of the shoulder.